Ultrasensitive label free electrical detection of insulin in neat blood serum. - Luo, X; Xu, M; Freeman, C; James, T; Davis, J (2013)
Electrical assays potentially offer a highly sensitive, cheap, portable, automated, and multiplexed means of protein biomarker detection, characteristics with an ability to underpin both disease stratification and the development of point of care diagnostics. Most conveniently applied in a reagent free manner, all sensitive assays such as these suffer, however, from profound problems when applied in complex fluids such as blood serum. We report herein, the development, and clinical application, of a highly sensitive and selective electrical insulin biosensor based on a chemisorbed zwittorionic polymer support and a novel reagentless sensing technique based on phase monitoring electrochemical impedance spectroscopy. The polymer adlayer is exceptionally effective in both reducing background response and maintaining receptive antibody binding efficacy, while the non-Faradaic analysis avoids potential interference from background electro-active molecules. Applied to the detection of even a low molecular weight protein (here, insulin), a linear range from 0.1 to 200 pM and an unprecedented femtomolar detection limit are possible in undiluted blood serum.